Paul and Seneca within the Ancient Consolation Tradition : A Comparison - Muir, Alex W., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
In this monograph, Alex W. Muir shows how Paul and Seneca were significant contributors to an ancient philosophical and rhetorical tradition of consolation. Each writer's consolatory career is surveyed in turn through close readings of key primary texts: chiefly Seneca's three literary consolations and 'Epistles'; and Paul's letters, 1 Thessalonians, 2 Corinthians, and Philippians. A final comparative dialogue highlights the pair's adaptations and innovations within this tradition.